147k views
1 vote
Q4 please help thanks

Q4 please help thanks-example-1
User Adrii
by
5.8k points

2 Answers

2 votes

Answer:

see explanation

Explanation:

The area of the shaded triangle = area of ΔABD - area of ΔADC

A of ΔABD =
(1)/(2) × AD × BD

A =
(1)/(2) ×
(√(2) )/(2) ×
(√(2) )/(2)

=
(2)/(8) =
(1)/(4)

--------------------------------------------------------------------------

A of ΔACD =
(1)/(2) × AD × DC

A =
(1)/(2) ×
(√(2) )/(2) ×
(√(3) )/(3)

A =
(√(6) )/(12)

-------------------------------------------------------------------------

shaded area =
(1)/(4) -
(√(6) )/(12)

=
(3)/(12) -
(√(6) )/(12) =
(3-√(6) )/(12)

User Shanyu
by
5.3k points
4 votes

Answer:


\large\boxed{A==(3-\sqrt6)/(12)\ cm^2}

Explanation:

The shaded region is the triangle with base b and height h.


b=BD-CD\to b=(\sqrt2)/(2)-(\sqrt3)/(3)=(3\sqrt2)/((2)(3))-(2\sqrt3)/((2)(3))=(3\sqrt2-2\sqrt3)/(6)\\\\h=AD\to h=(\sqrt2)/(2)

The formula of an area of a triangle:


A=(bh)/(2)

Substitute:


A=((3\sqrt2-2\sqrt3)/(6)\cdot(\sqrt2)/(2))/(2)=\left((3\sqrt2-2\sqrt3)/(6)\right)\left((\sqrt2)/(2)\right)\left((1)/(2)\right)\\\\\text{use the distributive property}\ a(b+c)=ab+ac\\\\=((3\sqrt2-2\sqrt3)(\sqrt2))/((6)(2)(2))=((3\sqrt2)(\sqrt2)-(2\sqrt3)(\sqrt2))/(24)\\\\\text{use}\ √(a)\cdot√(a)=a\ \text{and}\ √(ab)=√(a)\cdot√(b)\\\\=((3)(2)-2\sqrt6)/(24)=(2(3-\sqrt6))/(24)=(3-\sqrt6)/(12)

User Pondikpa Tchabao
by
5.9k points